2022
DOI: 10.1371/journal.pone.0268687
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the quality of HIV rapid testing practices in public antenatal health care facilities, South Africa

Abstract: Monitoring HIV prevalence using antenatal HIV sentinel surveillance is important for efficient epidemic tracking, programme planning and resource allocation. HIV sentinel surveillance usually employs unlinked anonymous HIV testing which raises ethical, epidemiological and public health challenges in the current era of universal test and treat. The World Health Organization (WHO) recommends that countries should consider using routine prevention of mother-to-child transmission of HIV (PMTCT) data for surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In South Africa, the HIV Prevention-of-Mother-to-Child (PMTC) programme has managed to detect and treat maternal HIV infections to ensure that unborn babies are not exposed to HIV. 51 However, the downside of PMTC programme is that it exposes women to the psychological burden of dealing with an HIV status while pregnant. 51 , 52 , 53 , 54 Fear of testing for HIV during pregnancy was also observed in a study conducted by Brittain Myer et al 55 in Cape Town, who found that pregnant women are afraid of taking Antiretrovirals (ARVs) because they will be forced to disclose their HIV status to their partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Africa, the HIV Prevention-of-Mother-to-Child (PMTC) programme has managed to detect and treat maternal HIV infections to ensure that unborn babies are not exposed to HIV. 51 However, the downside of PMTC programme is that it exposes women to the psychological burden of dealing with an HIV status while pregnant. 51 , 52 , 53 , 54 Fear of testing for HIV during pregnancy was also observed in a study conducted by Brittain Myer et al 55 in Cape Town, who found that pregnant women are afraid of taking Antiretrovirals (ARVs) because they will be forced to disclose their HIV status to their partners.…”
Section: Discussionmentioning
confidence: 99%
“… 51 However, the downside of PMTC programme is that it exposes women to the psychological burden of dealing with an HIV status while pregnant. 51 , 52 , 53 , 54 Fear of testing for HIV during pregnancy was also observed in a study conducted by Brittain Myer et al 55 in Cape Town, who found that pregnant women are afraid of taking Antiretrovirals (ARVs) because they will be forced to disclose their HIV status to their partners. This has led to cases of gender-based violence where pregnant women are blamed and beaten up for bringing HIV into the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate this transition in surveillance strategy, evaluations of routine data are required. A 2020 assessment of the national prevention-of-mother-to child programme concluded that South Africa was close to achieving the transition to routine data surveillance in relation to HIV testing, but that further evaluation of data completeness and accuracy was required (11,12). While these studies look speci cally at the validity of routine HIV testing data in comparison to laboratory-based HIV testing data from surveys, it should be emphasised that HIV patient management in South Africa is based on routine HIV point-of-care testing results.…”
Section: Introductionmentioning
confidence: 99%